Is use of CBCT without proper training justified in paediatric dental traumatology? An exploratory study - Gertrude Van Gorp; Arno Maes; Marjan Lambrechts; Reinhilde Jacobs; Dominique Declerck (BMC, 2023)
Abstract Background Proper skills in radiographic diagnosis are essential for optimal management of dental trauma. Aim To assess diagnostic accuracy obtained by paediatric dentists using Cone Beam Computed Tomography (CBCT) without specific training and to compare this with their performance using intraoral radiographs. Methods Intraoral and CBCT images of 89 teeth, spread over twenty dental trauma cases were presented in random order to nine paediatric dentists. Diagnostic findings were compared with those of a benchmark reference. Sensitivity and specificity were calculated and compared using paired t-tests. Results Overall, observers' diagnostic performance was rather poor with significantly higher sensitivity when using 2D images (P = 0.017). Performance differed considerably according to the type of pathology. Using either imaging modality, sensitivity for diagnosing apical pathology and root fractures was high while the opposite was seen for inflammatory root resorption, root cracks and subluxations. Statistically significant differences between imaging modalities were seen for root fractures (P = 0.013) and apical pathology (P = 0.001), in favor of 3D, and for crown fractures (P = 0.009) in favor of 2D. Conclusion Overall poor performance of paediatric dentists indicates that additional training in radiographic diagnosis is required. In order to justify the use of CBCT to increase diagnostic performance, proper training of the paediatric dentist is mandatory.